The Impact of Bilingualism on Executive Function: A Meta-Analysis - Ithriyah, Siti (Open Access Indonesia Journal of Social Sciences, 2024)
The potential cognitive benefits associated with bilingualism have garnered substantial attention in recent years. The present meta-analysis aimed to synthesize and critically evaluate the existing evidence regarding the impact of bilingualism on executive function (EF), a set of cognitive processes vital for goal-directed behavior. A comprehensive literature search was conducted across multiple databases, encompassing studies published between 2018 and 2024. Studies were included if they employed a quantitative design, compared bilingual and monolingual individuals on at least one measure of EF, and reported sufficient statistical data for effect size calculation. A total of 32 studies met the inclusion criteria, yielding a combined sample size of 3,875 participants. The overall meta-analysis revealed a small but significant positive effect of bilingualism on EF (Hedges' g = 0.18, 95% CI [0.12, 0.24], p < 0.001). Moderator analyses indicated that the effect was moderated by the type of EF assessed, with stronger effects observed for inhibitory control and cognitive flexibility than for working memory. In conclusion, our study suggests that bilingualism is associated with enhanced EF. The magnitude of the effect varies across different EF components, highlighting the need for further research to elucidate the specific mechanisms underlying the bilingual advantage in cognitive control.